2017
DOI: 10.1177/1541931213601925
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Information Sought by Caregivers of Alzheimer’s Patients on Online Peer-Support Groups

Abstract: Caregivers of Alzheimer's patients find respite in online communities for solutions and emotional support. This study aims to understand the characteristics of information caregivers of Alzheimer's 3 patients are searching for and the kind of support they receive through internet-based peer-4 support communities. Using a web crawler written in Python web programming language, we 5 retrieved publicly available 2500 random posts and their respective solutions from April 2012 to 6 October 2016 on the solutions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Of the types of dementia specified in this review, 35% of studies included dementia (7,(30)(31)(32)(33)(34)(35), 20% of studies included LBD (32,(35)(36)(37), 15% of studies included AD and other non-specific forms of dementia (30,32,35). However, 45% of studies did not specify the type of dementia (38)(39)(40)(41)(42)(43)(44)(45)(46). All 20 studies identified information needs irrespective of dementia types, however information seeking behaviour was only reported in 11 studies.…”
Section: Figure 1: Study Flow Diagrammentioning
confidence: 97%
See 4 more Smart Citations
“…Of the types of dementia specified in this review, 35% of studies included dementia (7,(30)(31)(32)(33)(34)(35), 20% of studies included LBD (32,(35)(36)(37), 15% of studies included AD and other non-specific forms of dementia (30,32,35). However, 45% of studies did not specify the type of dementia (38)(39)(40)(41)(42)(43)(44)(45)(46). All 20 studies identified information needs irrespective of dementia types, however information seeking behaviour was only reported in 11 studies.…”
Section: Figure 1: Study Flow Diagrammentioning
confidence: 97%
“…The three most commonly mentioned needs related to dementia were general information on dementia (10 studies, 62.5%) (34-37, 40-42, 44, 46, 47), dementia treatment (7 studies, 43.7%) (7,30,31,36,45,46,48) and identification and understanding of dementia symptoms and behaviour (6 studies, 37.5%) (7,37,42,44,45,48). Other information needs within this category also included dementia prognosis (6 studies, 37.5%) (7,31,35,39,41,43), current dementia medication (5 studies, 31.2%) (34,37,40,42,48), experimental drugs and clinical trials (4 studies, 25%), current research on dementia (3 studies, 18.7%) (36,37,46) and genetic aspects of dementia (2 studies, 12.5%) (37,48). The following information needs were mentioned only once (0.06%): negative impact of dementia on family and community (7), information specific to different stages of dementia (45), chance of recovery (7) and memory skills (37) ( Table 2).…”
Section: Disease-specific Informationmentioning
confidence: 99%
See 3 more Smart Citations